Privacy protection, data security and protection in technology utilization in home care services for the older people: A survey study of managers - Kuha, Suvi; Xiong, Essi; Hammarén, Mira; Ylisirniö, Minna; Haverinen, Jari; Suominen, Jarno; Leikas, Jaana; Kanste, Outi (Finnish Journal of eHealth and eWelfare, 2023)
The purpose of this study was to describe managers’ perceptions of privacy protection, data security and protection in technology utilization, related challenges, and solutions, and factors related not acquiring technological solutions in home care services for the older people. This cross-sectional survey study was conducted by electronic survey in Autumn 2022. The data was collected from the managers of home care services (n=68) from five public social and healthcare joint municipal authorities and fifteen municipalities or cities located in different parts of Finland. The questionnaire included four structured and two open questions. The data was analyzed using descriptive statistical methods and the principles of inductive content analysis. According to results, the issues raised by the Digi-HTA evaluations regarding data security and protection are mainly adequately considered when implementing technological solutions, but areas for development were also identified. According to managers’ evaluations, factors related to data protection are adequately considered in the technology acquisition processes, and criteria related to data security have been created for the processes. Not acquiring technological solutions was estimated to be especially influenced by the fact that the solutions did not meet the clients’ needs or were not seen to make operations more efficient. The managers’ perceptions of the challenges of privacy protection and data security and protection in technology utilization, were related to the operating environment, digital solutions, procedures, competence, and the organization’s practices in the prevention of challenges. The solutions to these challenges were seen as communication and interaction, defining processes of privacy protection, data security and protection, changing procedures, and developing competence. Taking account of factors related to privacy protection, data security and protection is mainly adequately implemented in home care services, though the challenges associated with them are perceived as diversified. The research identified a clear need for comprehensive training of all personnel, concrete evidence-based recommendations, and clear instructions of procedures. Particularly, attention should be paid to realizing the older people’s right to self-determination and ensuring informed consent.